2012
DOI: 10.1021/cg301129v
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Growth Modes of ALD ZnO

Abstract: The initial phases of the ALD growth of ZnO have been examined. It is shown that ZnO exhibits an island-like growth on Si, layer-by-layer on GaN, whereas on sapphire, the growth mode can be tuned by the deposition temperature. A new method for depositing ultrathin smooth polycrystalline films is presented. The growth rates on different substrates and at different deposition temperatures were analyzed, and the possibility of epitaxial growth was also examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 30 publications
10
59
0
Order By: Relevance
“…As depicted in figure 3(a), film growth is found to occur in two stages: a nonlinear surface nucleation/incubation stage and a linear growth stage. This growth behavior is consistent with that of conventional vacuum based ALD, which has been verified by in situ crystal microgravimetry(QCM) [22], scanning electron microscopy(SEM) [43], atomic force microscopy(AFM) [44], and surface profilometry [45]. The lack of growth during the initial deposition cycles is attributed to the nucleation time to form ZnO nuclei on the bare substrate [22].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…As depicted in figure 3(a), film growth is found to occur in two stages: a nonlinear surface nucleation/incubation stage and a linear growth stage. This growth behavior is consistent with that of conventional vacuum based ALD, which has been verified by in situ crystal microgravimetry(QCM) [22], scanning electron microscopy(SEM) [43], atomic force microscopy(AFM) [44], and surface profilometry [45]. The lack of growth during the initial deposition cycles is attributed to the nucleation time to form ZnO nuclei on the bare substrate [22].…”
Section: Resultssupporting
confidence: 77%
“…Methods to decrease nucleation time have included substrate pretreatment with oxygen plasma [43] or acid cleaning [45] to increase the hydroxyl density on the surface. More commonly, increasing the length of the precursor dose time results in an increase in ZnO nuclei formation consequently decreasing the nucleation time [44]. This effect has been reproduced by AP-SALD here, where it is seen in figure 3(a) that depositions done with quicker oscillation speeds and hence lower precursor dose times, require more deposition cycles to populate the surface with ZnO nuclei that subsequently grow into a continuous film and enter the linear growth regime.…”
Section: Resultsmentioning
confidence: 53%
“…So, this may be related to the lack of chemical bonding sites such as O-H groups on the surface of SiO 2 34. In previous study3536, it is reported that more ALD cycles are required for full coverage of the ZnO layer on SiO 2 surface, due to deficient O-H groups on the surface of the SiO 2 . In general, it is well known that the surface of untreated Al 2 O 3 is hydrophilic due to an abundance of hydroxyl (OH − ) groups.…”
Section: Resultsmentioning
confidence: 98%
“…In recent years, there has been an increasing interest in the growth of ZnO thin films by ALD method [12,13]. This method is a very promising deposition technique for semiconductor films since it has several practical advantages including precise thickness controllability, large area & large batch capability, good conformality and low process temperature.…”
Section: Introductionmentioning
confidence: 99%